Probing Students’ Research Skills: A case of the Utilizing Technology in The New Normal Era - Joey Ms. Suba; Edwin D. Torres; Jon Ivee P. Hernandez; Maribeth G. Rivera; Maybell L. L. Panlaqui; Lester G. Loyola (Jurnal Pengajaran MIPA, 2022)
Online delivery systems have been a booming industry worldwide because it has become an easy and safe way of acquiring necessities in our daily lives. This trend is the most recognized case of the application of information technology in the new normal era. Information technology major students’ skills in conducting research were identified Using the results of research related to the online delivery system. A slight difference was found between the information technology education major (preservice IT teachers) and the information technology major. However, the results cemented the importance of embedding research results in the IT major curriculum.